Planning for regional development : the capital region, Draft development plan. (Development planning series T1/2/3) - Government of the Republic of Trinidad and Tobago. Ministry of Finance, Planning and Development. (Town and Country Planning Division., 2011)
Describes the planning and development initiatives for the capital region, its geology, infrastructure, demography, economic structure, national development strategy and development proposals including industrial, tourist-related and community developments.